The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1126/scisignal.aal4064
|View full text |Cite
|
Sign up to set email alerts
|

Radiation inhibits salivary gland function by promoting STIM1 cleavage by caspase-3 and loss of SOCE through a TRPM2-dependent pathway

Abstract: Store-operated Ca2+ entry (SOCE) is critical for salivary gland fluid secretion. We report that radiation treatment caused persistent salivary gland dysfunction by activating a TRPM2-dependent mitochondrial pathway, leading to caspase-3–mediated cleavage of stromal interaction molecule 1 (STIM1) and loss of SOCE. After irradiation, acinar cells from the submandibular glands of TRPM2+/+, but not those from TRPM2−/− mice, displayed an increase in the concentrations of mitochondrial Ca2+ and reactive oxygen speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(64 citation statements)
references
References 46 publications
2
60
2
Order By: Relevance
“…This process is termed store operated Ca 2+ entry (SOCE) [25]. Calpain, γ-secretase and casepase-3 can cleave STIM1 thus regulating SOCE [21, 22, 26]. The Michalak group reported that calpain dynamically regulated STIM1 turnover and consequently SOCE through proteolysis of STIM1 proteins in both basal and apoptotic conditions.…”
Section: Disabling Channel Activities By Proteolysismentioning
confidence: 99%
See 1 more Smart Citation
“…This process is termed store operated Ca 2+ entry (SOCE) [25]. Calpain, γ-secretase and casepase-3 can cleave STIM1 thus regulating SOCE [21, 22, 26]. The Michalak group reported that calpain dynamically regulated STIM1 turnover and consequently SOCE through proteolysis of STIM1 proteins in both basal and apoptotic conditions.…”
Section: Disabling Channel Activities By Proteolysismentioning
confidence: 99%
“…In addition, it has been shown that in submandibular gland acinar cells, exposure to ionizing radiation led to caspase-3 activation and consequently STIM1 cleavage through a TRPM2-dependent pathway. Proteolysis of STIM1 further resulted in a marked loss of SOCE, and consequently decrease in fluid secretion [26]. In summary, proteolytic fragmentation of STIM1 by calpain, γ-secretase and caspase-3 regulates the amount of functional STIM1 on the ER membrane and hence the extent of Ca 2+ influx via the SOCE mechanism.…”
Section: Disabling Channel Activities By Proteolysismentioning
confidence: 99%
“…As TRPM2 has been reported to induce mitochondrial damage (Liu et al . ), the mitochondrial membrane potential was measured (ΔΨ m ) in WT and TRPM2 pancreatic acinar cells. Administration of 1 m m H 2 O 2 resulted in a marked drop of ΔΨ m in WT cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These changes led to a sustained decrease in STIM1 expression and consequently decreased the store‐operated Ca 2+ entry (Liu et al . ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation